Development of Mobile Ground Control System and GPS Base Auto Tracking Antenna - Irwanto , Herma Yudhi (BRIN Publishing, 2018)
Flight test of both rocket and high speed Unmanned Aerial Vehicle (UAV), which is currently developed by LAPAN, can not be separated from the need for a monitoring system of all the attitude of the vehicles. Utilizing and combining some of the available equipment components into a ground control system (GCS) equipped with GPS based auto tracking antenna, makes it easy in previous flight test activities that only do tracking antenna manually. This ground control system is equipped with automatic tracking antenna that always leads to the vehicle, so that the data attitude of flying the vehicle will be maximally monitored and analyzed directly with ease. This system has been tested on a laboratory scale related to testing using hardware in the loop simulation system